Gaps in the management of adrenal insufficiency in melanoma survivors: a retrospective cohort studyResearch in context - Wei Lin; Wei Wang; F. Stephen Hodi; Le Min (EClinicalMedicine)
Summary: Background: Due to limited data on managing immunotherapy-induced secondary adrenal insufficiency (SAI) in melanoma survivors, this study investigated its management strategies and outcomes. Methods: This retrospective cohort study analyzed melanoma patients treated with immune checkpoint inhibitors (ICIs) with SAI (Mel_SAI, n = 161), without SAI (Mel_CON, n = 168), and patients with pituitary adenoma-related SAI (Pit_SAI, n = 106) at our institution from January 2013 to November 2023. We compared glucocorticoid management patterns, quality of life using distress scores, and the impact of different glucocorticoid types on survival outcomes using Kaplan–Meier analysis. Findings: Mel_SAI received significantly higher initial (median: 30 mg; IQR: 20–30 mg) and maintenance (median: 25 mg; IQR: 20–30 mg) hydrocortisone doses than Pit_SAI (initial: 20 mg; IQR: 15–30 mg; maintenance: 15 mg; IQR: 15–23 mg). Over half of Mel_SAI received prednisone as initial glucocorticoid replacement (n = 89, 55%), compared to 27% (n = 29) of Pit_SAI. Distress scores were significantly higher in Mel_SAI (median: 3; IQR: 2–5) than in Pit_SAI (median: 2; IQR: 1–3), but similar between Mel_CON. Prednisone use was associated with decreased survival in Mel_SAI (hazard ratio: 2.31; 95% CI: 1.14–4.46). Interpretation: Higher glucocorticoid doses and prednisone use in melanoma patients with SAI may be due to higher distress scores rather than SAI itself. Given the negative impact on survival and potential side effects, we recommend hydrocortisone at standard doses as the preferred glucocorticoid replacement in melanoma patients with SAI. Funding: None.